Study of Dynamic Behaviour of Micro Bubbles in Distilled and Polluted Water - Winarto, F Eko Wismo (2010)
Abstract—The zigzag upward movement of millimeter size spherical air bubble in a vertical column water purification system adds undesired turbulence effect and acts as a suspended particle stirrer. Size reduction of air bubbles is one of the solutions to minimize the turbulence effect. Lifting up of the suspended particle require laminar rise-up of the air bubble. An experimental setup is established to study the development of small size air bubbles in a vertical water column. Porous sintered glass with porosities of 1 to 40 μm, are used to produce micro bubbles. Compressed air at a pressure of 27 kPa is forced through the diffuser to release bubbles at the bottom of the water column. The strategies to control the bubble size in monodispersed and polydispersed cases are discussed. Microbubble technique was used to remove suspended particles in polluted water. Bubble horizontal velocity diminishes when maximum air pressure reaches 22 kPa. By using Glycerin in various volume fractions of 0.1% to 0.5% and CMC (Carboxy Mectril Cellulose) as water pollutant, the relationships between air pressures, vertical and horizontal velocities, as well as bubble size are established. Keyword— Micro bubble, water treatment technique, diffuser, polydisperse, polluted water